2015
DOI: 10.1007/s12149-015-1018-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ultrasonography features and malignancy rate of toxic and nontoxic autonomous nodules: a preliminary study

Abstract: US features and malignancy potential of nontoxic autonomous nodules resemble toxic autonomous nodules. Lower diameter suggests that they can represent a preliminary stage of toxic ones and have potential of toxicity when get bigger in size. There is still a considerable risk of malignancy risk in autonomous nodules whether toxic or not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 26 publications
2
13
0
1
Order By: Relevance
“…They reported that toxic autonomous nodules were significantly bigger and had a significantly higher rate of microcalcification compared to nontoxic ones. 17 Smith et al demonstrated the overall cancer incidence as 18.3% for TNG, and they did not find any significant association with malignancy and age, preoperative dominant nodule size, lymphocytic thyroiditis or preoperative FNA. 3 In the present study, we found that hot nodules had a bigger nodule size and higher rate of presence of peripheral halo compared to cold and warm nodules, whereas micro-and macrocalcification of hot nodules were similar to cold nodules.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…They reported that toxic autonomous nodules were significantly bigger and had a significantly higher rate of microcalcification compared to nontoxic ones. 17 Smith et al demonstrated the overall cancer incidence as 18.3% for TNG, and they did not find any significant association with malignancy and age, preoperative dominant nodule size, lymphocytic thyroiditis or preoperative FNA. 3 In the present study, we found that hot nodules had a bigger nodule size and higher rate of presence of peripheral halo compared to cold and warm nodules, whereas micro-and macrocalcification of hot nodules were similar to cold nodules.…”
Section: Resultsmentioning
confidence: 94%
“…Dirikoc et al did not find any significant difference in terms of cytological diagnosis between toxic and nontoxic autonomous nodules except AUS/FLUS which was higher in the nontoxic group. 17 Cytology of the 19 hyperfunctional nodules was evaluated in a different study, and it was reported that cytology was benign in 10 (52.6%), AUS/FLUS in 6 (31.6%), and ND in 3 (15.8%) nodules. 29 In the present study, cytological results of hot, cold, and warm nodules were evaluated separately and found that of 364 hot nodules, 80 (22%) had ND, 259 (71.2%) has benign, 17 (3.6%) had AUS/FLUS, 2 (0.5%) had FN/SFN, 2 (0.5%) has SM, and 4 (1.1%) had malignant cytologies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations